Security for costs in ICC and ICSID arbitration - Stanivuković Maja D. (Zbornik Radova: Pravni Fakultet u Novom Sadu, 2015)
The Article is about security for costs in international arbitration under the ICC and ICSID Rules. It explains who is entitled to submit such a request, what kind of costs are secured, whether the tribunal has authority to order such measure, and the basis of such authority. This is followed by the discussion of the conditions for ordering the measure and the reasons that speak against it. Among various exceptional circumstances justifying the measure that are mentioned in arbitral case law, the following are discussed in more detail: manifest insolvency or bankruptcy of the claimant, SPV as claimant, third party financing of the claim, change of circumstances, respondent is not a signatory to the arbitration agreement, and probability that respondent will be awarded costs. Reasons speaking against the measure mentioned in the cases are the following: consent to the risk of insolvent claimant, access to arbitral justice, equity, respondent's bad faith, and untimeliness of the request. Finally, certain questions of procedure are discussed such as burden of proof and consequences of claimant's non-compliance with the order to pay security. The author concludes that in ICC and ICSID arbitration arbitrators are reluctant to order security for costs although such requests by respondents have become more frequent in recent times. The threshold respondent must pass to convince the tribunal that there are exceptional circumstances justifying the measure is high. The fact that claimant is insolvent alone does not suffice for the success of such request.